Analisis Motivasi Kerja, Lingkungan Kerja, dan Produktivitas Kerja Pegawai Pada Pusat Pengelolaan Pendapatan Daerah Wilayah Karawang - Putri Ayu Rukmini; Aji Tuhagana; Zenita Apriani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to find out and understand the results of the analysis of work motivation, work environment and employee work productivity at the Regional Revenue Management Center for the Karawang Region. The location of this research is the Regional Revenue Management Center for the Karawang Region. This research method uses a qualitative descriptive approach, expressed through word selection, sentence construction, detailed narrative and visual representation. Data collection techniques using interviews, observation and documentation. The results of research on work motivation provided at the Regional Revenue Management Center for the Karawang Region are quite good. The working environment at the Regional Revenue Management Center in the Karawang Region is still less comfortable for working employees, because several facilities were found to be not very functional. The work productivity of employees at the Regional Revenue Management Center for the Karawang Region can be seen from work efficiency, always trying to provide fast and precise services to the community, but increasing work productivity has not been achieved or is not yet optimal. In this way, of course, to increase employee work productivity at the Karawang Region Regional Revenue Management Center, it is necessary to pay attention to work motivation, especially the work environment so that it can leave a deep impression on employees, which will produce better results for employees.